2010
DOI: 10.1007/s10157-010-0382-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of connexin-mimetic peptides on perfusion pressure in response to phenylephrine in isolated, perfused rat kidneys

Abstract: This study showed that Cx43 plays a pivotal role in regulating renal vascular resistance and that Cx40 attenuates PE-induced vasoconstriction. These results provide new evidence that gap junctions may control renal circulation and vascular responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…Given that Panx3 has been shown to release ATP, a role for TGF regulation via purinergic signaling cascades cannot be excluded [16]. In contrast to previous studies [21,55,56], Piao and colleagues showed a pivotal role of Cx43 in perfusion pressure [37]. These discrepancies in the involvement of different Cx species in renal autoregulatory mechanisms could be related to different experimental settings and the stability of different blocking peptides.…”
Section: Autoregulation Of Renal Blood Flowcontrasting
confidence: 46%
See 1 more Smart Citation
“…Given that Panx3 has been shown to release ATP, a role for TGF regulation via purinergic signaling cascades cannot be excluded [16]. In contrast to previous studies [21,55,56], Piao and colleagues showed a pivotal role of Cx43 in perfusion pressure [37]. These discrepancies in the involvement of different Cx species in renal autoregulatory mechanisms could be related to different experimental settings and the stability of different blocking peptides.…”
Section: Autoregulation Of Renal Blood Flowcontrasting
confidence: 46%
“…The authors showed that Cx43 plays a pivotal role in regulating renal vascular resistance, as administration of 43 Gap26 significantly elevated perfusion pressure. In addition, infusion of 40 Gap27 considerably suppressed the increase in perfusion pressure induced by phenylephrine, indicating that Cx40 attenuates phenylephrine-induced vasoconstriction [37]. Finally, blocking peptides directed against Cx37, Cx40, Cx43 or Cx45 had no effect on conducted calcium responses in isolated rat interlobular arteries [38].…”
Section: Vascular-conducted Responsesmentioning
confidence: 93%
“…Thus, we strongly suggest that more than one type of Cx hemichannel is involved in the mHBSS-induced enhanced neuronal activity. Nevertheless, Cx43 appears to have a prominent role because the mHBSS-induced enhanced neuronal activity was drastically inhibited by Gap27, which is a well-known Cx43 hemichannel blocker (Piao et al, 2011; Wang et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…22) Using Tie-Cre recombinase and renin-Cre recombinase mice, Wagner et al reported that endothelial Cx40 is not essential for the control of systemic blood pressure and renin expression. 23) Thus, clarifying the molecular and subcellular mechanisms of Cx-mediated renal microcirculation in the pathophysiological settings awaits future studies, using refined methods of genetic engineering.…”
Section: Potential Roles Of Mesangial Cell–intercellular Communicatiomentioning
confidence: 99%